NEW CHANGES IN LABORATORY TESTS IN WOMEN WITH CHRONIC SALPINGOOPHORITIS COMPLICATED WITH PAIN SYNDROME - Ziyayeva E`tiborhon Rasuljonovna (Bright Mind Publishing, 2025)
Chronic pelvic pain syndrome is one of the complications of chronic salpingo-oophoritis, which in many cases causes disability and disruption of the life of sick women. Early diagnosis of this disease radically improves the results of treatment.
Keywords: Chronic pelvic pain syndrome, chronic salpingoophoritis, substance P.